2018
DOI: 10.1016/j.jaap.2018.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Consistency of biochar properties over time and production scales: A characterisation of standard materials

Abstract: Users of biochar in the field require this product to reliably meet its declared specifications.For the first time, this work investigated, whether these specifications could be reproducibly obtained as a sole function of the thermal history of the biomass feedstock during slow pyrolysis, irrespective of the type and scale of the production unit. Using volatile matter content as a proxy for a wider set of biochar quality parameters, biochar from units at scales from grams to hundreds of kilograms, representing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(67 citation statements)
references
References 41 publications
0
67
0
Order By: Relevance
“…Commercial standardized biochars were purchased from UK Biochar Research Centre. Chosen samples were produced from five different biomasses feedstock (Miscanthus, wheat straw, oil seed rape, rice husk, and mixed softwoods) using a pilot-scale rotary kiln pyrolysis unit [14] setting the highest treatment temperature (HTT) to 550 • C. Pyrolysis parameters and yields are summarized in Table 1 according to the producer data (further info on the feedstock can be found following the link in reference [15]). Two components BFA diglycidyl resin were purchased from CORES (Cores epoxy resin, LPL).…”
Section: Methodsmentioning
confidence: 99%
“…Commercial standardized biochars were purchased from UK Biochar Research Centre. Chosen samples were produced from five different biomasses feedstock (Miscanthus, wheat straw, oil seed rape, rice husk, and mixed softwoods) using a pilot-scale rotary kiln pyrolysis unit [14] setting the highest treatment temperature (HTT) to 550 • C. Pyrolysis parameters and yields are summarized in Table 1 according to the producer data (further info on the feedstock can be found following the link in reference [15]). Two components BFA diglycidyl resin were purchased from CORES (Cores epoxy resin, LPL).…”
Section: Methodsmentioning
confidence: 99%
“…Standard biochar material manufactured from rice husk was used (UK Biochar Research Centre, University of Edinburgh; Mašek et al, 2018). The rice husk was sourced from Sri Lanka and produced using the UK Biochar Research Centre Stage III Slow Pyrolysis Unit (rotary kiln pyrolyzer), described in Buss and Mašek (2014), at a highest treatment temperature of 700°C and a residence time in the heated zone of 20 min.…”
Section: Biocharmentioning
confidence: 99%
“…Cosentino et al [281] evaluated the performance of a standardized biochar set that was produced by UK Biochar Research Center [282], considering flexural strength and fracture energy. The authors reported inferior performances compared to those achieved by previous studies [283].…”
Section: Biochar-inorganic-based Compositesmentioning
confidence: 99%